Points of passage : Jewish transmigrants from Eastern Europe in Scandinavia, Germany, and Britain 1880-1914 /: Jewish transmigrants from Eastern Europe in Scandinavia, Germany, and Britain 1880-1914. (2013) - Unknown
No abstract available